2006
DOI: 10.1021/la053528w
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically Driven Protein Aggregation:  β-Lactoglobulin at Low Ionic Strength

Abstract: The aggregation of beta-lactoglobulin (BLG) at ambient temperature was studied using turbidimetry and dynamic light scattering in the range 3.8 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
173
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(198 citation statements)
references
References 60 publications
22
173
2
Order By: Relevance
“…This behaviour is consistent with the increase in the k D value for 5E when adding sodium chloride. Previous studies have found a strong correlation between increased aggregation rates and electrostatic selfassociation [13,55,80,99], which might also explain the increased aggregation of 5E.…”
Section: The Patch-charged Mutantsmentioning
confidence: 83%
See 2 more Smart Citations
“…This behaviour is consistent with the increase in the k D value for 5E when adding sodium chloride. Previous studies have found a strong correlation between increased aggregation rates and electrostatic selfassociation [13,55,80,99], which might also explain the increased aggregation of 5E.…”
Section: The Patch-charged Mutantsmentioning
confidence: 83%
“…For 5E, the salt-induced increase in k D reflects the presence of an electrostatic attraction between proteins [48,55,71]. This behaviour occurs when proteins have near net neutral charge and large anisotropic charge distributions, which likely arises in 5E, from engineering the negative charge patch on a positively charged scaffold.…”
Section: Protein-protein Interactions Characterized In Terms Of K Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of aggregation are very different, with Zn-free insulin at nonextreme pH conditions forming predominantly dimers, tetramers, hexamers, and higher order multimers, 59 while BLG forms dimers in equilibrium with much larger aggregates. 49 The possibility that these differences arise from the higher degree of charge asymmetry for BLG at pH near pI (a distinct positive domain coupled with a large and more diffuse negative domain, which leads to a tendency for highly nonlinear aggregation 49 ) is certainly a hypothesis worth further examination.…”
Section: Discussionmentioning
confidence: 99%
“…Although increases in the protein concentration commonly result in an increase in protein aggregation [7,27], some authors consider the opposite behavior due to the repulsion-attraction forces. The increase in concentration reduces the attraction forces, resulting in decreased protein-protein interactions and therefore the formation of aggregates [30].…”
Section: Influence Of Protein Concentrationmentioning
confidence: 99%